If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 80 = 0 Reorder the terms: 80 + 8x = 0 Solving 80 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-80' to each side of the equation. 80 + -80 + 8x = 0 + -80 Combine like terms: 80 + -80 = 0 0 + 8x = 0 + -80 8x = 0 + -80 Combine like terms: 0 + -80 = -80 8x = -80 Divide each side by '8'. x = -10 Simplifying x = -10
| 2x+15= | | 4x+5x=42x-4 | | 5(x-3)+2=5(2x-8)-3 | | 4(2)+48+46-3=4x+3x | | 12x^3-12x^2+24x-24=0 | | 10x-2=8x+14 | | 5(4(-2)+3)=6(3(-2)+2)-1 | | 5(4t+3)=6(3t+2)-1 | | x+20=3x+30 | | x-10=2x+20 | | 3x^2+12x-351=0 | | 4(3-x)+2x=-12 | | 15x-3=5x+7 | | m-7=15 | | 3(3k-5)=4(3k-1)-17 | | 5(2(8)-1)=4(2(8)+1)+7 | | 5(x-5)+5=10 | | 30x+6-7=8x | | 3(x-2)+7=5 | | 5(2m-1)=4(2m+1)+7 | | 4(-10)-7=3(2(-10)+5)-2 | | 4a-7=3(2a+5)-2 | | -14+7=5x-4x | | x^4-3x+2=0 | | 20x=16+5 | | 10c=26x-18y | | 8=5z-27 | | -5k-8=2(k+6)+1 | | 15+6x-3x=0 | | 11-8x=66-43x | | -90-10x=9x+24 | | 114-3x=3x+24 |